Developing methods to assess the relationship between ergometer and on-water rowing performance from independent datasets - Jones, S.; Bailey, C.; Thomas, D.; White, M. G. E.; Rees, P.; Summers, H. D.; Bezodis, N. E. (ISBS Proceedings Archive (Michigan), 2023)
Rowing ergometers are often used by internationally competitive athletes alongside on-water rowing. This study proposes methods to develop a generalisable relationship between maximal effort 2000 m ergometer and on-water rowing performance using independent datasets. Ergometer times for 2000 m tests (n = 153) and 2000 m on-water times from international races (n = 139) were collated. Percentiles from the raw data and fitted probability density functions were mapped to develop a generalisable performance relationship. Bootstrapping was utilised to estimate the uncertainty in the percentile mappings. When built on a larger sample of athletes, this approach could be useful to identify athletes who under or overperform on water compared to ergometers, and this could provide valuable context for future biomechanical investigations of rowing technique.